Insufficient intake of alpha-linolenic fatty acid (18:3n-3) during pregnancy and associated factors - Vasconcelos, Leticia Garcia [UNESP]; Gomes, Caroline de Barros [UNESP]; Malta, Maira Barreto; Dichi, Isaias; Benicio, Maria Helena D'Aquino; Barros Leite Carvalhaes, Maria Antonieta de [UNESP] (Pontificia Universidade Catolica Campinas, 2017)
Objective To analyze alpha-linolenic fatty acid intake in two cohorts of pregnant women, and to identify factors associated with alpha-linolenic acid intake. Methods This is a cohort study involving pregnant women with low obstetric risk (N=353) in public health system from a municipality of Sao Paulo state, Brazil. In each trimester, two 24-hour food recalls were collected. Descriptive analyses of dietary lipid profiles were performed, followed by a multiple comparison test. According to the trimester of pregnancy, differences were assessed using the mean difference test. To evaluate the adequacy of linoleic fatty acid and alpha-linolenic acid intake, the adequate intake test was used. The association between alpha-linolenic acid intake adequacy and maternal characteristics was investigated using a binary logistic regression model. Results Total lipids intake and the percentage contribution to dietary energy met recommended levels. One-third of the diets demonstrated a lower than daily recommended intake of alpha-linolenic acid. Overweight pregnant women were twice as likely to have inadequate alpha-linolenic acid intake. Pregnant women from a more disadvantaged socioeconomic situation had greater risks of inadequate intake. Conclusion Over-intake of lipids is not problematic, but quality is an issue, with one third of the pregnant women and their fetuses exposed to adverse effects due to low intake of omega-3 fatty acids, indicating important nutritional vulnerability in this population.
Keywords: Alpha-linolenic acid; Fatty acids, omega-3; Fatty acids, omega-6; Pregnant women